Systemic LPS and inflammatory response during consecutive days of exercise in heat - Barberio, M. D.; Elmer, D. J.; Laird, R. H.; Lee, K. A.; Gladden, B.; Pascoe, D. D. (International Journal of Sports Medicine, 2015)
This investigation studied circulating LPS activity, potential intestinal damage, and the systemic inflammatory response (SIR) during the exercise heat acclimation process. 8 healthy males (Age=24±3 years) ran in a hot environment on 5 consecutive days until core temperature (Tc) was elevated 2°C above rest. Plasma was obtained pre-, post-, 1 h post-, and 3 h post-exercise on the 1st, 3rd, and 5th day of exercise and analyzed for TNF-a, IL-6, IL-10, IL-1ra, LPS, and intestinal fatty acid-binding protein (I-FABP). Plasma LPS (1.1 EU·ml-1±0.1 vs. 0.7 EU·ml-1±0.03; P<0.01) and I-FABP (930.7 pg·ml-1±149.0 vs. 640.2 pg·ml-1±125.0; P<0.001) were significantly increased post-exercise each. The SIR remained largely unchanged during the study except for TNF-a. Plasma TNF-a was significantly lower on Day 5 at 1 h (3.2 pg·ml-1±0.6 vs. 4.5 pg·ml-1±0.8; P=0.01) and 3 h (3.6 pg·ml-1±0.8 vs. 4.8 pg·ml-1±0.9; P=0.05) post-exercise as compared to Day 1. Findings indicate that adaptations to exercise in the heat resulting in reductions of intestinal damage and plasma LPS activity require longer time periods in moderately trained males.